2006
DOI: 10.1002/elps.200500608
|View full text |Cite
|
Sign up to set email alerts
|

Chiral microemulsion electrokinetic chromatography with two chiral components: Improved separations via synergies between a chiral surfactant and a chiral cosurfactant

Abstract: In this study, the combination of two chiral components in a microemulsion formulation for the separation of enantiomers via microemulsion EKC (MEEKC) was successfully accomplished. Previous publications of chiral microemulsions have utilized only one chiral entity; the surfactant, cosurfactant, or oil was chiral. This is the first study, to date, of the effects of using two chiral species in a single pseudostationary phase (PSP). The chiral surfactant dodecoxycarbonylvaline (DDCV) was used in conjunction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…In addition to the use of a chiral surfactant [17][18][19][20][21][22] or a chiral cosurfactant 23 as the enantioselective element within the microemulsion droplets in MEEKC, the present study was demonstrated for a novel chiral-MEEKC system employing optically active (S)-(+)-2-octanol as a chiral oil for effecting the enantioseparation of basic drugs in MEEKC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the use of a chiral surfactant [17][18][19][20][21][22] or a chiral cosurfactant 23 as the enantioselective element within the microemulsion droplets in MEEKC, the present study was demonstrated for a novel chiral-MEEKC system employing optically active (S)-(+)-2-octanol as a chiral oil for effecting the enantioseparation of basic drugs in MEEKC.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,23 In addition, it is also recognized that organic modifiers can have an effect on the electroosmotic flow (EOF), the viscosity, the dielectric constant, the conductivity of the background electrolyte, and the solubility of the analytes. 27 Consequently, the effect of the 1-butanol concentration (4.4 to 8.8% (w/w)) on the enantioseparation of (±)-norephedrine was studied; and the obtained results can be seen in Fig.…”
Section: Influence Of the Cosurfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of two chiral components in microemulsion electrokinetic chromatography was investigated (170). By using an S-dodecoxycarbonylvaline with the cosurfactant S-2-hexanol, an increased resolution of 3.7 was achieved in the separation of pseudoephedrine enantiomers.…”
Section: Affinity and Interactionsmentioning
confidence: 99%
“…The next DDCV publication was the first to describe the simultaneous incorporation of two chiral selectors into one microemulsion; it was subsequently employed for the separation of N-methyl ephedrine and pseudoephedrine enantiomers [66]. Each chiral surfactant enantiomer (R-and S-DDCV) was combined with one enantiomer of a chiral cosurfactant (S-2-hexanol).…”
Section: Microemulsionsmentioning
confidence: 99%